2014
DOI: 10.1177/1479164114547703
|View full text |Cite
|
Sign up to set email alerts
|

Low-density lipoprotein cholesterol levels in adults with type 2 diabetes: An alternative equation for accurate estimation and improved cardiovascular risk classification

Abstract: Low-density lipoprotein cholesterol (LDL-C) is a major risk factor for atherosclerotic disease. Despite its limitations, Friedewald-calculated LDL-C (F-LDL-C) remains widely used for LDL-C determination. In this observational study of 1999 adults with type 2 diabetes mellitus (T2DM), we compare the accuracy of F-LDL-C to directly measured LDL-C (M-LDL-C) and derived and validated a new [SMART2D (Singapore Study of MAcro-angiopathy and Micro-Vascular Reactivity in Type 2 Diabetes)] formula to estimate LDL-C. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
3
8
0
Order By: Relevance
“…According to American Diabetes Association (ADA) guideline in diabetic patient without overt CVD, the goal of serum LDL-level is < 100 mg/dL [ 25 ]. By using 100 mg/dL as the threshold level, more than 10% of patients will be misclassified, if Friedwald formula compared to direct measurement of LDL-C is used, this is the same as results reported by Chai Kheng et al [ 24 ].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…According to American Diabetes Association (ADA) guideline in diabetic patient without overt CVD, the goal of serum LDL-level is < 100 mg/dL [ 25 ]. By using 100 mg/dL as the threshold level, more than 10% of patients will be misclassified, if Friedwald formula compared to direct measurement of LDL-C is used, this is the same as results reported by Chai Kheng et al [ 24 ].…”
Section: Discussionsupporting
confidence: 63%
“…Some studies on general population and diabetic patients have shown that Friredwald formula give significantly higher results compared to direct method [ 14 ]. In a study on diabetic patients same result was obtained [ 22 ] but in two separate studies on diabetic patient, Friedewald equation showed negative bias which this issue can be very important in values near the cutoff points [ 23 , 24 ]. According to American Diabetes Association (ADA) guideline in diabetic patient without overt CVD, the goal of serum LDL-level is < 100 mg/dL [ 25 ].…”
Section: Discussionsupporting
confidence: 54%
“…The tendency for FF values of c-LDL-C to misclassify people with various LDL levels, especially at higher levels of TG is seen in the literature. 13,17,[19][20][21] In a study of 1999 adults with type-2 diabetes, more than 10% of patients were misclassified by the c-LDL-C by the FC method for LDL target of 100 mg/dL compared to a modified equation. 16 This was more pronounced in people with TG >203 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…FE as the most widely applied method in clinical practice is recommended in several guidelines related to the therapy of dyslipidemia. 11,12,15,16 It assumes the ration of the mass of TG to very low-density lipoprotein cholesterol (VLDL-C) to be relatively constant. 8 However, in the real world, the ratios are variable in different individuals leading to less accuracy of FE, especially in the population with TG > 4.5 mmol/L and non-fasting state.…”
Section: Discussionmentioning
confidence: 99%
“…FE as the most widely applied method in clinical practice is recommended in several guidelines related to the therapy of dyslipidemia . It assumes the ration of the mass of TG to very low‐density lipoprotein cholesterol (VLDL‐C) to be relatively constant .…”
Section: Discussionmentioning
confidence: 99%